Prevalence, Molecular Characterization, and Antibiotic Susceptibility of Cronobacter sakazakii Isolates from Powdered Infant Formula Collected from Chinese Retail Markets - Fei, Peng; Jiang, Yichao; Jiang, Yan; Yuan, Xiujuan; Yang, Tongxiang; Chen, Junliang; Wang, Ziyuan; Kang, Huaibin; Forsythe, Stephen J. (Frontiers in Microbiology, 2017)
Cronobacter sakazakii is an opportunistic pathogen that causes severe infections in neonates and infants through contaminated powdered infant formula (PIF). Therefore, the aim of this study was a large-scale study on determine the prevalence, molecular characterization and antibiotic susceptibility of C. sakazakii isolates from PIF purchased from Chinese retail markets. Two thousand and twenty PIF samples were collected from different institutions. Fifty-sixt C. sakazakii strains were isolated, and identified using fusA sequencing analysis, giving a contamination rate of 2.8%. Multilocus sequence typing (MLST) was more discriminatory than other genotyping methods. The C. sakazakii isolates were divided into 14 sequence types (STs) by MLST, compared with only 7 clusters by ompA and rpoB sequence analysis, and 4 C. sakazakii serotypes by PCR-based O-antigen serotyping. C. sakazakii ST4 (19/56, 33.9%), ST1 (12/56, 21.4%), and ST64 (11/56, 16.1%) were the dominant sequence types isolated. C. sakazakii serotype O2 (34/56, 60.7%) was the primary serotype, along with ompA6 and rpoB1 as the main allele profiles, respectively. Antibiotic susceptibility testing indicated that all C. sakazakii isolates were susceptible to ampicillin-sulbactam, cefotaxime, ciprofloxacin, meropenem, tetracycline, piperacillin-tazobactam, and trimethoprim-sulfamethoxazole. The majority of C.sakazakii strains were susceptible to chloramphenicol and gentamicin (87.5% and 92.9%, respectively). In contrast, 55.4% C.sakazakii strains were resistant to cephalothin. In conclusion, this large-scale study revealed the prevalence and characteristics of C. sakazakii from PIF in Chinese retail markets, demonstrating a potential risk for neonates and infants, and provide a guided to effective control the contamination of C. sakazakii in production process.